1976
DOI: 10.1037/0022-006x.44.3.330
|View full text |Cite
|
Sign up to set email alerts
|

Patient characteristics and outcome in psychotherapy and behavior therapy.

Abstract: Ninety-four psychoncurolic or personality disordered patients received 4 months of analytically oriented psychotherapy, behavior therapy, or waiting list treatment. Neither active treatment was more effective than the other with any type of symptom (including affective ones), although both were more consistently effective than the wailing list. With psychotherapy, relatively greater success was associated with less overall pathology on the Minnesota Multiphasic Personality Inventory and higher socioeconomic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1978
1978
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…If this is the case, such a finding would be in keeping with research by Sloane et al (1975) on short-term dynamic individual psychotherapy versus behavior therapy 9 In reviewing the results on patient characteristics and outcome they conclude:…”
Section: Discussionmentioning
confidence: 62%
“…If this is the case, such a finding would be in keeping with research by Sloane et al (1975) on short-term dynamic individual psychotherapy versus behavior therapy 9 In reviewing the results on patient characteristics and outcome they conclude:…”
Section: Discussionmentioning
confidence: 62%
“…In addition, there was no control condition that could be classified as either treatment as usual, waiting list or no treatment Petersen 2008 Randomised trial comparing a specialised psychotherapeutic day-treatment programme with a waiting list control condition for adults with personality disorder. Excluded because a diagnosis of AsPD was an exclusion criterion Sloane 1976 Randomised trial comparing psychoanalytically-oriented psychotherapy, behaviour therapy and wait-list controls in outpatients. Excluded because diagnosis of AsPD not attempted Springer 1995 Randomised trial comparing DBT-derived CBT group therapy with discussion control group for inpatients with PD, assessed using MCMI-II.…”
Section: Characteristics Of Included Studies [Ordered By Study Id]mentioning
confidence: 99%
“…Had the investigation measured general preference only, it would not have been possible to note female preferences for behavioural therapy given a specific phobia even though gestalt therapy was generally preferred under forcedchoice conditions. It is interesting to note that the female subjects seemed to recognize what recent research has demonstrated in terms of higher outcome rates for a phobia-behaviour modification match (Sloane et al, 1976). Their willingness to choose an intervention which appeared more appropriate for a specific problem, has important heuristic implications for continuing research on therapist-client-modality matching.…”
Section: Discussionmentioning
confidence: 82%